Association between Refractive Errors and Anemia: A Cross Sectional Study in Basra, Iraq - Al-Badran , Ihsan Mardan (Hammurabi Journal of Medical Sciences, 2024)
Background: anemia is a major global health problem that has major effects on human vision. Objectives: a concurrent presence of refractive errors has been identified in anemic children, which requires investigating this intriguing association. Material and Methods: this study used 100 children through clinical evaluations to establish whether they had refractive errors or not besides checking their anemic states. Results: this study found that children with anemia are 4.31 times more likely to develop refractive errors than those who do not have (95% CI: [confidence interval], p < 0.05), which means there is strong statistical evidence for this claim. Conclusion: there could be some connection between anemia and refractive errors thus challenging the idea of mere coincidence. Therefore, further investigation has been carried out to find out what exactly causes such correlations between these two conditions.